Remanent Magnetization in Portland-Cement-Based Materials - Bidegain, Juan Carlos (1999)
The purpose of this research is to demonstrate the possibility of applying one geophysical method to studying untraditional systems as is the case with Portland-cement-based materials. The research demonstrates how conventional paleomagnetic methodology can be employed in studying the mode of magnetic recording in present-day industrial materials. Portland-cement admixtures such as fly ashes and furnace slags should be discriminated, because those particles interact in soils and sediments in nature. Moreover, a better undertanding of magnetic remanent acquisition in model materials can serve to improve the interpretation of magnetic remanent acquisition in natural rocks formed a long time ago. The magnetic constituents of Portland-cement paste and mortar acquire a magnetic remanence due to their alignment with the earth's magnetic field at the casting place. This magnetization can be measured using ordinary paleomagnetic techniques. The alignment of the individual magnetic particles accounts for the intensity of the magnetic remanence, which can be increased by adding water and by vibration before setting and hardening. Blast furnace slag admixtures also add to the enhancement of the intensity of remanence. The magnetization of Portland-cement-based materials shows a near linear relationship with the water /cement (w/c) ratios employed in the experimental work; the w/c ratios range between 0.2 – 0.6 in pastes and 0.3 – 0.6 in mortar. Stable remanent magnetization was obtained during the first seven days of setting and hardening, a period necessary for magnetic particles to become locked parallel to the earth's magnetic field. The stability of magnetic remanence predicts the usefulness of the methodology in studying the properties of Portland cement and particularly in the control of iron-bearing admixtures.